Faktor-Faktor yang Mempengaruhi Faktor-Faktor yang Mempengaruhi Efektivitas Manajemen Risiko K3 pada Proyek Pembangunan BTS - Robert Panjaitan, Juliantri; Hasibuan, Bernard; Sugiarto, Sugiarto (Syntax Corporation, 2025)
This study aims to analyze the factors influencing the effectiveness of Occupational Safety and Health (OSH) risk management in Base Transceiver Station (BTS) construction projects at PT Adyawinsa Telecommunication & Electrical. The research is motivated by the high incidence of workplace accidents in the telecommunications construction sector, particularly due to falls from height. A quantitative approach was employed using survey methods with questionnaires distributed to 169 respondents from the Telco Solution Services Division. Eight independent variables were tested: management commitment, training, safety culture, communication, supervision, regulatory compliance, work environment, and technology adoption. The effectiveness of OSH risk management was assessed as the dependent variable, based on the implementation of the HIRADC method aligned with ISO 45001:2018 and Government Regulation No. 50 of 2012. Multiple linear regression analysis revealed that management commitment, training, supervision, and regulatory compliance significantly influence OSH risk management effectiveness. The coefficient of determination (R²) of 0.513 indicates that these four variables account for 51.3% of the variance in risk management effectiveness. This study concludes that the success of OSH risk management is influenced not only by formal policies but also by active managerial involvement and regulatory adherence. The findings provide practical insights for the industry in developing data-driven and preventive OSH strategies.